Antioxidative and angiotensin converting enzyme inhibitory activities of Schizophyllum commune mycelial extract / Noor Hasni Mohd Fadzil - Noor Hasni, Mohd Fadzil (2018)
Schizophyllum commune is an edible mushroom known as the split gill mushroom that possessed various nutritional and medicinal properties. In this study, S. commune mycelia biomass was cultivated in shake (SHFM) and static (STFM) flask culture conditions for 14 days in Glucose-yeast-malt-peptone media. Freeze dried mycelia biomass was then extracted by solvents, polysaccharide and protein extraction methods producing 11 extracts for each culture condition. Antioxidant assays of the extracts gave different effect on different assays, for SHFM, in Folin-Ciocalteu assay, cold water extract (CWE) showed highest phenolic content with 7.80±0.25 mg GAE/g extract. On the other hand, STFM protein fraction obtained by precipitation with 90% ammonium sulphate (F90) gave highest phenolic content with 15.04±0.39 mg GAE/g extract. In DPPH scavenging activity, CWE from both SHFM and STFM conditions gave highest scavenging activity (20.94±1.93% and 16.93±2.65%) and IC50 of 38.46 mg/ml and 17.24 mg/ml respectively. In cupric ion reduction antioxidant capacity (CUPRAC), protein fraction F90 of both SHFM and STFM conditions gave highest absorbance value of 0.420±0.00 and 0.064±0.00 at 450 nm respectively. CWE of SHFM condition gave highest percentage of metal chelating activity with 67.51±0.77% while PE of STFM scored 30.02±1.23%. For inhibition of lipid peroxidation assay, HWE from both culture conditions showed highest inhibition percentage with 26.40±0.57% and 20.07±0.78%. The LCMS/MS analysis of extracts with potent antioxidant activity of each assays showed that, CWE-SH contained compounds such as tryptophan, gluconic acid and phenolic acid, while in CWE-ST compounds such as 2(3,4-dihydroxyphenyl)-7-hydroxy-5-benzene propanoic acid, gluconic acid and quinic acid conjugate were present. HWE-SH contained compounds such as phenolic acid while HWE-ST contained compounds such as propanoic acid, gluconic acid, quinic acid conjugate, phenylvaleric acids and protocatechuic acid. Preliminary antihypertensive activity of S. commune using Angiotensin-Converting-Enzyme kit demonstrated that at 100 μg/ml, WRE-SH have the highest inhibition (58.20±1.81%) for SHFM, while PE-ST (56.67±1.79%) for STFM. LCMS analysis of WRE-SH exhibited the presence of compounds such as hydroxylated cinnamic acid, tryptophan, leucine and thiamine. Four extracts that showed high ACE inhibition activity (WRE-SH, CDME-ST, PE-ST and F90-ST) were selected for further separation using a ultracentrifugal filter unit with nomial molecular weight limit cut-off at 10 000 Da. Each >10 kDa and <10 kDa extracts produced were subjected to ACE inhibitory assay. Highest ACE inhibition at 50 μg/ml was demonstrated by F90-ST <10 kDa with 30.0% inhibition. This fraction was subjected to SDS PAGE analysis and resolved protein bands were processed for LCMS-QTOF protein analysis. Results revealed two putative antihypertensive proteins named carboxypeptidases and alpha/beta hydrolase proteins; and a few putative uncharacterized proteins that may have anti hypertensive property.